CRADLE TO CRADLE IN URBAN PLANNING - Kusumo, Camelia (DIMENSI (Journal of Architecture and Built Environment), 2012)
Cradle to Cradle is a well-known sustainability concept introduced by Braungart and McDonough. It is a concept about how a product can be designed from the outset so that, after their useful lives, they will provide nourishment for something new, thus “waste equals food” (Braungart and McDonough, 2002). This eco-effective principle has been applied widely in products development; however, it is less known in the urban planning discipline where sustainable development is the main ‘key word’ in transforming the urban area. The question that this paper expands on is whether it is possible to apply the Cradle to Cradle concept into urban planning practice. This article explains the difference between the eco-efficient concept and the eco-effective concept and elaborate from there on a possibility to apply the Cradle to Cradle principle to urban planning practice. It is shown that the Cradle to Cradle principle offers an instrument for bringing complex sustainable concepts within reach of planning thinking and discussion, and for generating alternatives which may not otherwise be given serious consideration.